Adsorção de Cr (VI) em coluna de leito fixo utilizando hidroxiapatita – hidrotalcita dopada com nanotubo de carbono como adsorvente - PEREIRA, Clarissa Cruz (2019)
The hydrotalcite (HT) and hydroxyapatite (HAp) materials are minerals with adsorptive and catalytic properties, while carbon nanotubes (CNT) are nanomaterials capable of improving physical, chemical and electrical characteristics of various materials. The aim of the present work was to synthesize the HAp-HT material and to dope it with two different proportions of NTC (5 and 15% w/w) in order to apply it as Cr (VI) adsorbent in acid medium. The HAp-HT material was synthesized by the coprecipitation method, with pH variable 10≤pH≤11, being doped with CNT and subjected to ultrasonic bath and hydrothermal treatment (80 ° C / 24h). The characterization through the techniques: XRD, SEM/EDS, FT-IR, Raman and Physisorption of N2. The adsorption study was performed in a fixed bed column, under conditions: T = 40 and 60 ° C, Q = 2mL/min, t = 10h. The data were confirmed and there was an improvement in the material quality in 66%, with an insertion of CNT. As micrographs of the HAp-HT/CNT5 and HAp-HT/CNT15 samples, they presented larger crystals in size (5 μm), whereas the semi-qualitative chemical analysis of all the samples indicated a Ca/P ratio different from 1.67 (HAp Stoichiometric) and Mg/Al~3 (stoichiometric HT). In the FTIR and Raman spectra were recorded the main bands belonging to the phases HAp and HT, were tenuous deviations with the insertion of the CNT, probably caused by the molecular interactions between the phases HAp-HT and the CNT. Surface area increase (~ 78%) was recorded in the BET/BJH analysis, comparing the HAp-HT/CNT15 sample with HAp-HT. In the modeling of the adsorbed amount curves x time, an L-type isotherm was obtained, the parameters were better adjusted to the Freundlich isotherm (R2 = 0.92), the parameters indicated higher site heterogeneity in the samples doped with CNT (nHAp-HT = -3.4893, nHAp-HT/CNT5 = -1.7389, nHAp-HT/CNT15 = -1.6460) whereas the highest KL value was recorded in HAp-HT/CNT15 (KL=5.73x1014), this sample also presented better performance, with 60% higher retention than the HAp-HT material at 60 ° C. The kinetic modeling of the system was adjusted in the first and second order models, presenting better correlation of the data in the second order model (R2 = 0.99). The most efficient sample, HAp-HT / NTC15, presented little variation in k (4.3 x 10-4 min-1) and higher amount of solute adsorbed (7575.06 mg.g-1).